2022
DOI: 10.1186/s12931-022-02282-5
|View full text |Cite
|
Sign up to set email alerts
|

Higher circulating Trimethylamine N-oxide levels are associated with worse severity and prognosis in pulmonary hypertension: a cohort study

Abstract: Background Trimethylamine N-oxide (TMAO), the gut microbiota-dependent metabolite, is a potential biomarker in several cardiovascular diseases. However, no study has investigated its value in pulmonary hypertension (PH). Therefore, this study aimed to explore the association between plasma TMAO levels and prognosis in patients with PH. Methods Inpatients with idiopathic/heritable pulmonary arterial hypertension (IPAH/HPAH), PAH associated with cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 36 publications
(40 reference statements)
1
11
0
Order By: Relevance
“…The increase in TMAO levels may be responsible for the detrimental effects thought to originate directly from choline [ 29 , 30 ]. We have demonstrated that TMAO levels are associated with poor prognoses in patients with PH [ 9 ] and that pulmonary vascular remodelling in monocrotaline-induced PH rats was ameliorated after TMAO decreased, followed by the regulation of proliferation, apoptosis, and vasodilator pathways [ 8 ]. Additionally, TMAO has been reported to aggregate PH by inducing macrophage/monocyte chemokines and cytokine production [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The increase in TMAO levels may be responsible for the detrimental effects thought to originate directly from choline [ 29 , 30 ]. We have demonstrated that TMAO levels are associated with poor prognoses in patients with PH [ 9 ] and that pulmonary vascular remodelling in monocrotaline-induced PH rats was ameliorated after TMAO decreased, followed by the regulation of proliferation, apoptosis, and vasodilator pathways [ 8 ]. Additionally, TMAO has been reported to aggregate PH by inducing macrophage/monocyte chemokines and cytokine production [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the potential role of metabolism in the initiation and progression of PH as studies have suggested the presence of metabolic disturbances in patients with PH [ 6 ]. Our previous work also revealed that aberrant metabolism, characterised by elevated plasma TMAO and betaine levels, is associated with greater disease severity and worse prognoses in patients with PH and may serve as potential surrogate biomarkers for PH [ 7 9 ]. Choline—a precursor of TMAO—is a critical micronutrient that participates in various physiological processes, and it serves as an independent predictor of various cardiovascular disorders, such as hypertension [ 10 ], atherosclerosis [ 11 ], and myocardial infarction [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, TMAO inhibition can enhance cardiovascular disease prognosis ( 26 28 ). Notably, TMAO has become a prognostic indicator for various cardiovascular diseases, including atherosclerosis, heart failure, and pulmonary arterial hypertension ( 29 32 ). However, some studies have indicated that excessive SCFAs can induce Th1 and Th17 cell proliferation, which promotes inflammation ( 33 ), while some TMAO precursors have been found to exert protective effects on the cardiovascular system ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…The observed relative reductions in Faecalibacterium, Roseburia and Fusicatenibacter in CTEPH patients [34], also associated with reductions in endotoxin, were potential causes of increased gut inflammation and permeability [42,53,54]. Thus, metabolic endotoxaemia due to translocation of endotoxin induced by gut dysbiosis, which is already implicated in chronic low-grade inflammation in other cardiovascular diseases [39], may have a role in the pathogenesis of CTEPH.…”
Section: Lipopolysaccharidesmentioning
confidence: 98%